Shifting the Balance of Power: The Strategic Use of the CRPD by Disabled People’s Organizations in Securing ‘a Seat at the Table’ - Laufey Löve; Rannveig Traustadóttir; James Rice (Laws, 2019)
The article highlights how the strategic use of the Convention on the Rights of Persons with Disabilities (CRPD) by disabled people’s organizations (DPOs) in Iceland has produced a shift in the balance of power with regard to how, and by whom, disability legislation and policy in Iceland is developed. The article draws on a study examining the last stages of a consultative process between representatives of DPOs and policymakers in Iceland leading up to the adoption, in May of 2018, of core disability legislation, Laws pertaining to services for disabled people with long-term support needs (No. 38/2018). It examines the process from the perspective of representatives of DPOs through in-depth interviews and document analysis. This article draws on critical theory and the human rights approach in its analysis, with a particular emphasis on the roadmap to the coproduction of policy provided by the CRPD and the UN CRPD Committee through the issuance of guidance to States Parties to the Convention. It draws attention to the DPOs’ ongoing refocusing of their strategies, and their emphasis on harnessing the rights contained in the CRPD to gain recognition of their right to participation in the coproduction of policy and in changing process norms.